Fixed effects bias in panel data estimators - Hielke Buddelmeyer; Paul H. Jensen; Umut Oguzoglu; Elizabeth Webster (Institute for the Study of Labor (IZA), 2008)
Since little is known about the degree of bias in estimated fixed effects in panel data models, we run Monte Carlo simulations on a range of different estimators. We find that Anderson-Hsiao IV, Kiviet's bias-corrected LSDV and GMM estimators all perform well in both short and long panels. However, OLS outperforms the other estimators when the following holds: the cross-section is small (N = 20), the time dimension is short (T = 5) and the coefficient on the lagged dependent variable is large (? = 0.8).
urn:nbn:de:101:1-2008052773
Keywords: C23; 330; Panel data; LSDV; dynamic model; fixed effects; Panel; Methode der kleinsten Quadrate; Schätztheorie; Theorie